2018
DOI: 10.1096/fj.201701455rr
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac fibroblast‐specific p38α MAP kinase promotes cardiac hypertrophy via a putative paracrine interleukin‐6 signaling mechanism

Abstract: Recent studies suggest that cardiac fibroblast-specific p38α MAPK contributes to the development of cardiac hypertrophy, but the underlying mechanism is unknown. Our study used a novel fibroblast-specific, tamoxifen-inducible p38α knockout (KO) mouse line to characterize the role of fibroblast p38α in modulating cardiac hypertrophy, and we elucidated the mechanism. Myocardial injury was induced in tamoxifen-treated Cre-positive p38α KO mice or control littermates via chronic infusion of the β-adrenergic recept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 76 publications
(131 reference statements)
2
60
0
Order By: Relevance
“…Vice versa, in hypertrophic cardiomyopathy, mutations in sarcomeric proteins in cardiomyocytes can lead to increased profibrotic gene expression and proliferation of non-myocytes (170). This vicious cell interaction circle was recently confirmed by demonstrating that activation of p38α in adult cardiac fibroblasts, under β-adrenergic receptor stimulation, leads to IL-6 secretion that paracrinely causes cardiomyocyte hypertrophy (171). On the other hand, stimulation of protein kinase A in cardiomyocytes leads to CTGF and VEGF secretion that paracrinely induce collagen production and fibroblast proliferation leading to fibrosis (172).…”
Section: Cardiomyocyte-cardiac Fibroblast-macrophage Interactionsmentioning
confidence: 86%
“…Vice versa, in hypertrophic cardiomyopathy, mutations in sarcomeric proteins in cardiomyocytes can lead to increased profibrotic gene expression and proliferation of non-myocytes (170). This vicious cell interaction circle was recently confirmed by demonstrating that activation of p38α in adult cardiac fibroblasts, under β-adrenergic receptor stimulation, leads to IL-6 secretion that paracrinely causes cardiomyocyte hypertrophy (171). On the other hand, stimulation of protein kinase A in cardiomyocytes leads to CTGF and VEGF secretion that paracrinely induce collagen production and fibroblast proliferation leading to fibrosis (172).…”
Section: Cardiomyocyte-cardiac Fibroblast-macrophage Interactionsmentioning
confidence: 86%
“…The overexpression of miR‐214 suppressed the phosphorylation of p38 in bone marrow‐derived mesenchymal stem cells, 51 while it increased the cellular proliferation and phosphorylation of ERK induced by isoproterenol (β‐adrenergic receptor agonist) in cardiac fibroblast 52 . Furthermore, the absence of p38α MAP kinase, which was phosphorylated by isoproterenol, in cardiac fibroblast suppressed the isoproterenol‐induced elevation of miR‐214 53 . The functional role of miR‐199/214 in oxidative stress warrants further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Both in vitro and in vivo findings have suggested that p38 MAPK may play a role in the pathogenesis of renal fibrosis, acting downstream of TGF-β (Stambe et al, 2004). In models of cardiac injury, fibroblast-specific loss of p38 MAPK attenuated fibrotic and hypertrophic remodeling (Molkentin et al, 2017;Bageghni et al, 2018). Other studies have suggested that the MAPK kinase kinase (MAPKKK) TGF-activated kinase (TAK1) stimulates a matrix-synthetic fibroblast phenotype in vitro (Ono et al, 2003) and in vivo (Guo et al, 2013), presumably acting upstream of MAPKs.…”
Section: The Molecular Signals Involved In Tgf-β-mediated Fibrosismentioning
confidence: 99%